Upcycling Brewers' Spent Grain: The Development of Muffins and Biomarker Response After Consuming Muffins for 8-Weeks in Healthy Adults From Randomized-Controlled Trial. (29th May 2020) - Combest, Shannon; Warren, Cynthia; Patterson, Mindy
Abstract: Objectives: Brewers' spent grain (BSG), the most abundant by-product of the brewing industry, consist of malted barley residue leftover from beer production and are rich in fiber and protein. This study examined whether regular consumption of upcycled BSG flour can modulate blood biomarkers of cardiovascular disease (CVD), glucose homeostasis, inflammation, and body composition in healthy adults. Methods: Muffins containing 7.5 g BSG (20% wt: wt flour), 11.2 g BSG (30% wt: wt flour), and 0 g BSG (control) were developed and tested for consumer acceptability on overall liking, appearance, texture, moistness, sponginess, and taste. BSG muffins that maintained mean ratings of 5 or higher on a 9-point hedonic scale were considered acceptable and included in a feeding trial. A single-blind, randomized, placebo-controlled human feeding trial compared consumption of muffins with 12 g BSG (30%) or 0 g BSG daily for 8 weeks. BSG and control muffins were similar in total calories (BSG: 306 kcal, control: 307 kcal) and available carbohydrates (BSG: 51.2 g, control: 52.0 g). Fasting blood was collected for glucose, insulin, and lipid measurements and body composition was assessed using air displacement plethysmography at baseline and 8-weeks. During the 8 weeks of intervention, participants recorded 3-day food logs, 2-day stool logs to monitor changes in bowel movements and symptoms, and daily muffin consumption. Results: Consumer testing ( n = 107) found significant differences among appearance (F = 7.728, P = .001) and taste (4.947, P = .008) ratings across all muffins. Control (6.74 ± 1.84) and 20% (6.64 ± 1.90) muffins received higher appearance ratings and higher taste ratings for 20% muffins (7.15 ± 1.72). Additionally, 30% muffins had acceptability. In the feeding trial, 18 participants (26.8 ± 4.0 y) with a BMI of 23.4 ± 3.2 kg/m 2 completed the study. Systolic blood pressure (BP) ( P = .044) and insulin ( P = .011) were lower in the BSG group than the control group after consuming study muffins for 8-weeks. There were no significant treatment effects for glucose concentrations or body composition outcomes between test groups or over time. Conclusions: Consuming BSG reduces systolic BP and insulin in healthy adults compared to control muffins. A higher BSG dosage or consuming BSG for a longer duration may be necessary to observe additional clinical endpoints. Funding Sources: Moore-Khourie Fund.